2019
DOI: 10.18358/np-29-2-i103108
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Receiving Antenna Using Mechanism of Electrokinetic Phenomenon "Flow Potential"

Abstract: Предложен способ модификации мишени для МАLDI-МS-анализа, позволяющий селективно выделять аналиты из биологических образцов непосредственно на поверхности мишени, как альтернатива классическим методам. Для модификации мишени суспензию металл-аффинного сорбента на основе оксида железа(III) в 50% водно-метанольном растворе электрораспыляли в бескапельном режиме c динамическим делением потока жидкости при атмосферном давлении в нормальных условиях. МАLDI-мишень выступала в качестве противоэлектрода. На МАLDI-мише… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The authors have earlier considered in [1,2] and other papers the acoustoelectric conversion based on such an electrokinetic phenomenon as electroosmosis. In [3] there was suggested an acoustoelectric conversion based on the electrokinetic phenomenon reverse to electroosmosis, i. e. flow potential that is sometimes referred to as current potential [4]. Analysis of studies [1][2][3] showed that in both the cases of direct and reverse conversion almost identical mathematical and physical models are applicable, which is caused by the conversion reversibility and, hence, by the reversibility of electrokinetic transducers.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The authors have earlier considered in [1,2] and other papers the acoustoelectric conversion based on such an electrokinetic phenomenon as electroosmosis. In [3] there was suggested an acoustoelectric conversion based on the electrokinetic phenomenon reverse to electroosmosis, i. e. flow potential that is sometimes referred to as current potential [4]. Analysis of studies [1][2][3] showed that in both the cases of direct and reverse conversion almost identical mathematical and physical models are applicable, which is caused by the conversion reversibility and, hence, by the reversibility of electrokinetic transducers.…”
mentioning
confidence: 99%
“…is the external bulk force that is the source of the process of flow potential [3], η and ζ are the dynamic and bulk viscosities, respectively, ρ e is the electric charge density induced by the presence of a double layer in electrokinetic processes, ε is the dielectric permeability, ε 0 is the electric constant, ζ is the electrokinetic potential (zeta-potential), σ is the fluid conductivity. Index 0 corresponds to the electroosmosis process generated by the DC electric field E 0 , parameters without indices correspond to the remaining processes whose sources are the external acoustic field, flow potential, and also pump-induced fields.…”
mentioning
confidence: 99%
See 3 more Smart Citations